Hubungan Emosi Negatif, Pemulihan Kepuasan, dan Kepercayaan pada Konsumen Shopee Indonesia - Andriana, Ana Noor; Bharata, Wira (Journal of Business Management Education (JBME), 2021)
The phenomenon of the many cases and problems that occur related to the COD payment system on Shopee e-commerce is the basis for this research. The researcher tries to describe the concept of Recovery Service by connecting several attributes such as Negative Emotions, Recovery Satisfaction, and Trust. The population in this study are Shopee e-commerce consumers in Indonesia. The sampling technique used was the quota sampling method with a total sample of 110 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis method used in this research is Generalized Structured Component Analysis (GSCA). The results of the study stated that all hypotheses proposed in this study were accepted.